2005
DOI: 10.1152/ajprenal.00419.2004
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of superoxide anion and nitric oxide on blood pressure and renal hemodynamics in transgenic rats with inducible malignant hypertension

Abstract: Superoxide anion contributes to the pathogenesis of various forms of hypertension, but its role in the development of malignant hypertension remains unclear. The present study was performed to determine the influence of superoxide anion on blood pressure and renal hemodynamics in transgenic rats with inducible malignant hypertension [strain name: TGR(Cyp1a1Ren2)]. Malignant hypertension was induced in male Cyp1a1-Ren2 rats (n = 6) through dietary administration of the aryl hydrocarbon, indole-3-carbinol (0.3%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
61
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(77 citation statements)
references
References 33 publications
16
61
0
Order By: Relevance
“…Thus, the severe phenotype induced by the high dose of I3C is characteristic of malignant hypertension. 9,23,[31][32][33][34] Dietary administration of high-dose I3C did not alter either systolic blood pressure (144±5 vs. 147±6 mmHg) or body weight 307±10 vs. 322±6 g) of transgene-negative rats, indicating that the I3C-induced hypertension and weight loss were not the result of non-specific effects of I3C. Indeed, chronic administration of the AT 1 -receptor antagonist, candesartan, prevented the development of hypertension and loss of body weight in Cyp1a1-Ren2 transgenic rats induced with high-dose I3C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the severe phenotype induced by the high dose of I3C is characteristic of malignant hypertension. 9,23,[31][32][33][34] Dietary administration of high-dose I3C did not alter either systolic blood pressure (144±5 vs. 147±6 mmHg) or body weight 307±10 vs. 322±6 g) of transgene-negative rats, indicating that the I3C-induced hypertension and weight loss were not the result of non-specific effects of I3C. Indeed, chronic administration of the AT 1 -receptor antagonist, candesartan, prevented the development of hypertension and loss of body weight in Cyp1a1-Ren2 transgenic rats induced with high-dose I3C.…”
Section: Resultsmentioning
confidence: 99%
“…22 To induce malignant hypertension, group 3 rats (n=7) were fed a higher dose of I3C (0.3%, w/w; diet TD 00554, Harlan-Teklad) as described previously. 23 For this group, we had initially planned to induce with high-dose I3C for 14-15 days (i.e. for a duration comparable to the low-dose induction group); however, the rats induced with the higher dose of I3C exhibited severe loss of body weight, extreme lethargy, piloerection, and assumption of hunched posture which necessitated early termination of dietary I3C treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, this model allows induction of ANG II-dependent hypertension of graded severity using a benign and naturally occurring dietary supplement without the need for surgical intervention, dietary salt manipulation, or the administration of steroids (23,27). In essence, the Cyp1a1-Ren2 transgenic rat model is particularly advantageous because of the ease and reproducibility of genetically clamping expression of the Ren2 gene and inducing increases in plasma renin activity, plasma and intrarenal ANG II levels, and hypertension of graded severity (22,27,28,31,32).We have demonstrated that at a dose of 0.3% (wt/wt), chronic dietary administration of I3C induces malignant hypertension in Cyp1a1-Ren2 transgenic rats (27,28,31,32). Malignant hypertension is a severe form of hypertension characterized by rapidly increasing blood pressure, pressure diuresis and natriuresis, severe renal vasoconstriction and ischemia, activation of the renin-angiotensin system, microangiopathy, hemolytic anemia, and development of retinopathy (23,47,48).…”
mentioning
confidence: 99%
“…Accordingly, this model allows induction of ANG II-dependent hypertension of graded severity using a benign and naturally occurring dietary supplement without the need for surgical intervention, dietary salt manipulation, or the administration of steroids (23,27). In essence, the Cyp1a1-Ren2 transgenic rat model is particularly advantageous because of the ease and reproducibility of genetically clamping expression of the Ren2 gene and inducing increases in plasma renin activity, plasma and intrarenal ANG II levels, and hypertension of graded severity (22,27,28,31,32).…”
mentioning
confidence: 99%